2007
DOI: 10.1097/bot.0b013e3180ce833e
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Deltoid-Splitting Approach to the Proximal Humerus

Abstract: The recent technological developments in implant design and the wider availability of bone graft substitutes have stimulated a renaissance in the operative treatment of complex proximal humeral fractures. However, one of the remaining problems of the operative treatment of these injuries has been the limited surgical access to the posterior aspect of the shoulder afforded by the deltopectoral approach. In this article, we describe a novel extended deltoid-splitting approach, in which the area traversed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
1
51
1
Order By: Relevance
“…The deltopectoral approach requires extensive soft tissue dissection and muscle retraction to gain adequate exposure to the lateral aspect of the humerus [10,11,14,16,18-20]. This can cause further devascularization of fracture fragments during dissection and plating, leading to the disruption of critical blood supplies to the humeral head [10,18-20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deltopectoral approach requires extensive soft tissue dissection and muscle retraction to gain adequate exposure to the lateral aspect of the humerus [10,11,14,16,18-20]. This can cause further devascularization of fracture fragments during dissection and plating, leading to the disruption of critical blood supplies to the humeral head [10,18-20].…”
Section: Introductionmentioning
confidence: 99%
“…This can cause further devascularization of fracture fragments during dissection and plating, leading to the disruption of critical blood supplies to the humeral head [10,18-20]. The deltoid splitting approach, which is an alternative method, provides good visualization of the posterolateral aspect of the shoulder without extensive soft tissue dissection or forcible retraction; however, there is an increased risk of injuring the axillar nerve as compared to the conventional deltopectoral approach [16,21,22]. Recently, many studies have demonstrated the superiority of MIPO techniques via anterolateral deltoid splitting combined with skin incisions for the management of proximal humerus fractures [15,17,19,21-28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach improves access to fracture fragments, facilitates optimal plate positioning, and may help to preserve any remaining blood supply 18,43 to the proximal humerus. Detailed knowledge of the course of the anterior branch of the axillary nerve is required to minimize risk of damage during this approach.…”
Section: Choice Of Surgical Approachmentioning
confidence: 98%
“…More recently, an extended deltoid splitting approach has been described, using either a straight lateral 12,16,17 or shoulder strap 43,45,46 skin incision, with careful protection of the anterior branch of the axillary nerve. This approach improves access to fracture fragments, facilitates optimal plate positioning, and may help to preserve any remaining blood supply 18,43 to the proximal humerus.…”
Section: Choice Of Surgical Approachmentioning
confidence: 99%